Circadian Sleep/Wake Rhythm Abnormalities as a Risk Factor of a Poststroke Apathy. Issue 5 (July 2015) - Cosin, Charlotte; Sibon, Igor; Poli, Mathilde; Allard, Michèle; Debruxelles, Sabrina; Renou, Pauline; Rouanet, François; Mayo, Willy
Background: Poststroke apathy affects 19–55% of patients following stroke and has a negative impact on functional recovery, general health, and quality of life, as well as being a source of significant burden for caregivers. Aims: A major clinical issue is the delayed diagnosis of post-stroke apathy, and so the aim of our study is to evaluate the relationship between early poststroke alterations of circadian rhythms of sleep/wake cycles and the occurrence of poststroke apathy. Methods: Forty-six patients with a recent magnetic resonance imaging confirmed stroke were included. Main exclusion criteria were a mild to severe disability impeding home discharge from the hospital and the presence of apathy or dementia before stroke. Cerebrovascular lesions were evaluated by magnetic resonance imaging. At hospital discharge, an actigraph was used to measure patient's global activity as well as parameters of circadian rhythmicity (relative amplitude, interdaily stability, intradaily variability) and sleep (sleep duration, sleep efficiency, fragmentation index) over seven-days. Apathy was assessed at hospital discharge as well as at three-months using the Apathy Inventory and the Lille Apathy Rating Scale. Results: Of the 46 patients evaluated, 10 (22%) showed apathy three-months after stroke (median Apathy Inventory = 4·5). Before inclusion, these 10 subjects did not differ significantly from other patients concerning their sleep and, at inclusion, they did not differ concerning apathy, anxiety, depression, or cognitive and functional abilities. However, actigraphy measured at discharged identified significant alterations of sleep ( P < 0·005). Future poststroke apathy patients exhibited a decrease in sleep efficiency (actual sleep time expressed as a percentage of time in bed) and an increase in the fragmentation index (degree of fragmentation during the sleep period) at three-months. No association was observed between poststroke apathy and the characteristics of cerebrovascular lesions (stroke location, extent of leucoencephalopathy, number of lacunes and microbleeds). Conclusion: These results indicate that early poststroke alterations of sleep/wake circadian rhythms — easily evaluated by actigraphy — are associated with a higher risk of poststroke apathy at three-months. In terms of clinical outcomes, our results provide targets for very early identification of patients at risk to develop apathy after stroke and for assessing when to start specific therapy to optimize rehabilitation efficiency.